2019
DOI: 10.1590/1984-70332019v19n2a28
|View full text |Cite
|
Sign up to set email alerts
|

Control of plant height by 24 alleles at 12 quantitative trait loci in rice

Abstract: Plant height (PH) is controlled by quantitative trait loci (QTLs) in rice. In the present study, a recombinant inbred line population developed by crossing two rice cultivars, Lemont and Yangdao4, was grown in eight environments for QTL analysis. Multiple interval mapping detected 53 PH-QTLs, 39 of which clustered at 12 chromosome regions/putative loci. An examination of the 12 putative loci identified 24 alleles that are simultaneously involved in controlling PH. Linear regression analyses suggested that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The majority of the QTL found in this study were mapped to regions that were similar to those found in earlier studies [16,[128][129][130][131][132][133][134]. According to many studies (including those by Lanceras et al in [138], and Xu et al in 2020 [139]), chromosome 1 has the highest concentration of QTLs for PH (qPHC1.1). Most of the QTLs connected to grain yields were found on chromosomes 5 and 6 (qTPBC6.2, qFGC5.1, qFGD5.1, and qFGC6.2) [45,127,131,[140][141][142].…”
Section: Discussionsupporting
confidence: 84%
“…The majority of the QTL found in this study were mapped to regions that were similar to those found in earlier studies [16,[128][129][130][131][132][133][134]. According to many studies (including those by Lanceras et al in [138], and Xu et al in 2020 [139]), chromosome 1 has the highest concentration of QTLs for PH (qPHC1.1). Most of the QTLs connected to grain yields were found on chromosomes 5 and 6 (qTPBC6.2, qFGC5.1, qFGD5.1, and qFGC6.2) [45,127,131,[140][141][142].…”
Section: Discussionsupporting
confidence: 84%
“…In addition, higher activity of the SBI significantly reduced the rice PH, and, therefore, its application in rice production contributed to breed improved lodging-resistant rice varieties and thus increased yield. Although several studies on associations between markers and the plant height have been conducted in rice [ 10 , 30 , 31 , 32 , 33 ], to date, no report has documented a QTL analysis of the relationships between plant height and its components traits (panicle length and the length of all internodes), using two mapping strategies.…”
Section: Introductionmentioning
confidence: 99%